2007
DOI: 10.1007/s00468-007-0157-8
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic structure of Scots pine (Pinus sylvestris (L.)) needles during ageing and autumnal senescence

Abstract: Needle ageing and senescence were studied in Scots pine (Pinus sylvestris) trees growing in natural conditions with minimal anthropogenic influence. The four existing needle generations were analyzed by light and transmission electron microscopy before and during autumnal yellowing of the oldest needle generation. The change from green to yellow occurred within less than 4 days in central Finland. The structure of the oldest needles remained largely intact as long as they were green. Increase in mitochondrion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
2
6
1
Order By: Relevance
“…The activity was not affected by the treatments, however. The annual increase in phloem cells with needle age has been reported also earlier in Pinus sylvestris (L.) needles (Paramesvaran, 1971;Kivimäenpää and Sutinen, 2007) but not in xylem tissue as we observed here. The number of sclerenchyma cells or that of phloem rows was not affect by the treatments or the needle age.…”
Section: Discussionsupporting
confidence: 71%
“…The activity was not affected by the treatments, however. The annual increase in phloem cells with needle age has been reported also earlier in Pinus sylvestris (L.) needles (Paramesvaran, 1971;Kivimäenpää and Sutinen, 2007) but not in xylem tissue as we observed here. The number of sclerenchyma cells or that of phloem rows was not affect by the treatments or the needle age.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, the first mesophyll layer was not always representative for every structural characteristic and every treatment. This is in agreement with the findings of Kivimäenpää and Sutinen (2007) who reported that mesophyll cells near the epidermis of four year old needles of Pinus sylvestris had smaller chloroplasts with lower area of starch grains than cells in the inner part of the needle. Furthermore, Senser et al (1975) noticed in Picea abies that the chloroplasts in cells near to the epidermis had higher amounts of starch than cells near the central cylinder, according to the gradient in light intensity.…”
Section: Discussionsupporting
confidence: 93%
“…Autumnal litterfall did not take place before the BVOC sampling from the forest floor in Suonenjoki in the study year. The oldest needle generation (fourth in the study region) senesces, i.e., rapidly turns yellow, at the end of August -beginning of September, and drops later in Suonenjoki region (Kivimäenpää and Sutinen 2007). However, some needles from the lower parts of the canopy can drop earlier during the growing season, which was observed in all provenances here.…”
Section: Discussionmentioning
confidence: 49%